A Grammatical Analysis of the Syntactic Structure among English and Arabic Languages - ASSAL, Abdelkader (My University, 2020)
Syntax is a set of laws that determine the word order, and basically the architecture of the sentence within the different languages. This research aims to shed light on the syntactic analysis of the Quranic sentences. It aspires to work on a comparative study between Arabic and English languages syntax. The linguistic model used in this research is developed by Chomsky in 1950s, namely Phrase Structure Rules. The latter is a theory that represents a rewriting rule which describes the components of the sentence in a given language. The mean aim of this work is to examine and exhibit the situations where the two languages are different and similar in. The study is performed rigorously throughout a corpus of 11 selected sentences of different Quranic verses. Then, these sentences are represented in tree diagrams where the Arabic version of the same English sentence is separated in one table. Afterwards, the tables are divided according to each rule taken from the modal. An explanatory note is written below the tables to indicate the major remarks. The results show that Phrase structure Rules found some issues and problems in light of Arabic nominal sentences, barely certain sentences follow the same word order, especially some imperative, affirmative, and negative sentences.
case study of selected sentences from the holy Quran